Performance of the HYPERSCINT scintillation dosimetry research platform for the 1.5 T MR-linac. (21st February 2023) - Uijtewaal, Prescilla; Côté, Benjamin; Foppen, Thomas; de Vries, Wilfred; Woodings, Simon; Borman, Pim; Lambert-Girard, Simon; Therriault-Proulx, François; Raaymakers, Bas; Fast, Martin
Abstract: Objective. Adaptive radiotherapy techniques available on the MR-linac, such as daily plan adaptation, gating, and dynamic tracking, require versatile dosimetric detectors to validate end-to-end workflows. Plastic scintillator detectors (PSDs) offer great potential with features including: water equivalency, MRI-compatibility, and time-resolved dose measurements. Here, we characterize the performance of the HYPERSCINT RP-200 PSD (MedScint, Quebec, CA) in a 1.5 T MR-linac, and we demonstrate its suitability for dosimetry, including in a moving target. Approach. Standard techniques of detector testing were performed using a Beamscan water tank (PTW, Freiburg, DE) and compared to microDiamond (PTW, Freiburg, DE) readings. Orientation dependency was tested using the same phantom. An RW3 solid water phantom was used to evaluate detector consistency, dose linearity, and dose rate dependence. To determine the sensitivity to motion and to MRI scanning, the Quasar MRI 4D phantom (Modus, London, ON) was used statically or with sinusoidal motion ( A = 10 mm, T = 4 s) to compare PSD and Semiflex ionization chamber (PTW, Freiburg, DE) readings. Conformal beams from gantry 0° and 90° were used as well as a 15-beam 8 × 7.5 Gy lung IMRT plan. Main results. Measured profiles, PDD curves and field-size dependence were consistent with the microDiamond readings with differences well within our clinical tolerances. The angular dependence gave variations up to 0.8% when not irradiating directly from behind the scintillation point. Experiments revealed excellent detector consistency between repeated measurements (SD = 0.06%), near-perfect dose linearity ( R 2 = 1) and a dose rate dependence <0.3%. Dosimetric effects of MRI scanning (≤0.3%) and motion (≤1.3%) were minimal. Measurements were consistent with the Semiflex (differences ≤1%), and with the treatment planning system with differences of 0.8% and 0.4%, with and without motion. Significance. This study demonstrates the suitability of the HYPERSCINT PSD for accurate time-resolved dosimetry measurements in the 1.5 T MR-linac, including during MR scanning and target motion.